Fracture characteristics of round bamboo (Dendrocalamus asper) loaded in compression / Mohd Nazarudin Zakaria, Mansur Ahmad and Kamarulzaman Nordin - Zakaria, Mohd Nazarudin; Ahmad, Mansur; Nordin, Kamarulzaman (2004)
A study was conducted to determine the fracture characteristics of round bamboo and their relationship to the strength properties loaded in compression parallel to grain. The species of bamboo used, was "Buloh Betong" (Dendrocalamus asper).The modes of failure were observed to have three types namely splitting and compression (mode 1), multiple failure (mode 2) and compression and end rolling (mode 3). Mode 1 posses the highest strength value The values of Mode J, Mode 2 and Mode 3 are 69.48 N/mm2 , 68.83 N/mm2 and 57.25 N/mm2 respectively However, statistically the compression strength between mode of failure is not significantly difference. On the other hand, the effects of portion along the length of the culm and between node and internode on compression strength were found to be significant. The compression strength is higher at the top portion compared to the bottom.